2021
DOI: 10.1007/s41061-021-00347-5
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine in Drug Discovery: A Versatile Scaffold for Novel Biologically Active Compounds

Abstract: The five-membered pyrrolidine ring is one of the nitrogen heterocycles used widely by medicinal chemists to obtain compounds for the treatment of human diseases. The great interest in this saturated scaffold is enhanced by (1) the possibility to efficiently explore the pharmacophore space due to sp3-hybridization, (2) the contribution to the stereochemistry of the molecule, (3) and the increased three-dimensional (3D) coverage due to the non-planarity of the ring—a phenomenon called “pseudorotation”. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 85 publications
(114 reference statements)
1
88
0
Order By: Relevance
“…Based on the literature survey, it has been suggested that compared to pyrrole analogs, pyrrolidine scaffold will be having more preference to the drug design because of unrestricted conformation of the ring [ 172 ]. Further, pyrrolidine analog has privileged N − 1 position for substitutions which were present in US FDA-approved drugs [ 173 ].…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
“…Based on the literature survey, it has been suggested that compared to pyrrole analogs, pyrrolidine scaffold will be having more preference to the drug design because of unrestricted conformation of the ring [ 172 ]. Further, pyrrolidine analog has privileged N − 1 position for substitutions which were present in US FDA-approved drugs [ 173 ].…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
“…Initially, pyrrole was identified as a coal tar component in 1834, however it was isolated 23 years later from the pyrolysate of a bone (16). Pyrrole is characterized as an aromatic five membered N-containing heterocycle, differing in several key physicochemical parameters when compared to its saturated analogpyrrolidine (Table 1) (17).…”
Section: Pyrrole -Pharmacology Profile and Anticancer Propertiesmentioning
confidence: 99%
“…19 The interest in non-planar scaffolds has given rise to numerous developments in synthetic methods. [20][21][22][23][24] In FBDD programs, planar fragments are often avoided, since they tend to bind multiple targets, and therefore are potentially more difficult to develop into a selective drug-like compound. 16 Nonetheless, the successful ligand design from flat fragments has fueled the debate, demonstrating that the flatness of the fragments does not necessarily transfer to the lead.…”
Section: Three Dimensionalitymentioning
confidence: 99%